THE INTERNET LANGUAGE USES FOUND IN TAYLOR SWIFT AND HARRY STYLES’ TWEETS: A GENDER PERSPECTIVE STUDY - Yaski Ramadhanty Siregar; Katharina Rustipa (Dinamika Bahasa dan Budaya, 2020)
The goal of this study is to compare the language uses between two different genders who are communicating in twitter. The data were taken from Taylor Swift and Harry Styles’ tweets; 50 random tweets from each gender were collected to be analyzed. The data were analyzed using internet language theory by Danet (2001). The descriptive and qualitative method was used. The result showed that two similarities found in their tweets; there were four types of internet language they took and two were not used. While, the two singers also created several differences, such as; most of Taylor Swift’s internet language was emoticon while Harry Styles was capital letter, Taylor Swift used eight types and Harry Styles only five out eleven, and the last was that Taylor Swift succeeded to type 154 numbers of data but Harry Styles typed 259 data. The researcher concluded that Taylor Swift who reflected as women, turned out to be more expressive and chose more forms of language than men. While Harry Styles who represented as men tended to be assertive, did not like to express his feeling, and use fewer types. The study is important to know how different gender communicate to make a good relationship in social life. Key Words: langugage, gender, internet language uses, tweet